The effects of experimental training on starting performance in an elite breaststroke swimmer - A case study - Beretic, I. (Serbian Journal of Sports Sciences, 2013)
The aim of this study was to verify a method of exercises as part of an experimental training program devised to improve starting performance in elite senior swimmers. The testing procedure was conducted on one subject, an elite Serbian breaststroke swimmer, and it consisted of six starts. Initial measurements with advanced diagnostic equipment were conducted to determine errors in the starting technique. A special 8-week experimental program was designed consisting of three different exercises, with the purpose to correct the key components in performing an efficient start. After 8 weeks of the experimental training, final measurements were conducted. A repeated measure analysis of variance (ANOVA) was applied to determine significant differences for each variable between the initial and final testing sessions. The most significant finding of this research was the statistical difference in T15m variable.